Congenital diaphragmatic hernia: a case series in tertiary care centre - Basak, Aniruddha; Dipanka Debnath (International Journal of Contemporary Pediatrics, 2023)
Congenital diaphragmatic hernia (CDH) is characterized by a defect in the diaphragm leading to the protrusion of abdominal contents into the thoracic cavity affecting the normal development of the lungs. The prevalence of CDH ranges between 1:2000 and 1:4000 live births; it accounts for 8% of all major congenital anomalies. Approximately 90% of diaphragmatic defects occur posterolaterally and 80% are left-sided. The severity of the condition varies widely, the degree of pulmonary hypoplasia and pulmonary hypertension largely determining outcome. Gross was the first person who reported a series of successful repairs in 1946 with 100% survival and over the next 40 years, CDH was considered the quintessential neonatal surgical emergency. Since then, despite advances in neonatal intensive care, anaesthesia, and surgery, the overall survival rate has remained just around 50%. The management of CDH patients should be multidisciplinary. Prompt mechanical ventilation and imaging ensured favorable outcome after operative repair. The prognosis of CDH patients depends on the age of presentation and the mode of transport of the newborn baby to the tertiary hospital with pediatric surgery set-up.